Tapping into financial synergies: Alleviating financial constraints through acquisitions - Williamson, Rohan; Yang, Jie (Journal of Corporate Finance, 2021)
This paper examines whether firms are able to use acquisitions to ease their financial constraints. The results show that acquisitions do ease financing constraints for constrained acquirers. Relative to unconstrained acquirers, financially constrained firms are more likely to use undervalued equity to fund acquisitions and to target unconstrained and more liquid firms. Using a propensity score matched sample in a difference-in-difference framework, the results show that constrained acquirers become less constrained post-acquisition and relative to matched non-acquiring firms. This improvement is more pronounced for diversifying acquisitions and constrained firms that acquire rather than issue equity and retain the proceeds. Following acquisition, constrained acquirers raise more debt, increase investments, and reduce cash holdings relative to matched non-acquirers, consistent with experiencing reductions in financing constraints. These improvements are not seen for unconstrained acquirers. Finally, the familiar diversification discount is non-existent for financially constrained acquirers.